Pemodelan Alat Vein Finder dengan Penerapan Teknologi Berbasis Raspberry Pi dan Fitur Otomatis Penandaan Vena (VenaMark) - Niko Azhari Hidayat; Salsa Indramaharani; Aulia Putri Fatiha; Nabila Farah Azzah; Syafir Garega (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
Vein finder is a crucial visualization tool in the medical field, especially for patients with difficult vein access. This study presents the development of a vein finder device named VenaMark, utilizing Raspberry Pi 4 Model B. The system not only displays real-time vein images using an infrared camera but is also equipped with an innovative feature: an automatic ink pen that directly marks the vein location on the patient’s skin. This feature aims to assist medical personnel in accurately determining injection or blood draw points without guessing. The system integrates digital image processing technology and precise mechanical actuators to move the marker pen based on the vein detection output. Testing results show increased efficiency and accuracy in medical procedures, along with reduced patient discomfort caused by failed needle insertions.